2017
DOI: 10.1016/j.is.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking real-time vehicle data streaming models for a smart city

Abstract: The information systems of smart cities offer project developers, institutions, industry and experts the possibility to handle massive incoming data from diverse information sources in order to produce new information services for citizens. Much of this information has to be processed as it arrives because a real-time response is often needed. Stream processing architectures solve this kind of problems, but sometimes it is not easy to benchmark the load capacity or the efficiency of a proposed architecture. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…A recent study utilized Apache Kafka for stream processing. Fernandez-Rodriguez et al proposed real-time data streaming for vehicles in a smart city [ 69 ]. Their results revealed that Apache Kafka achieved a greater scalability, faster response, and reduced cost compared to traditional systems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study utilized Apache Kafka for stream processing. Fernandez-Rodriguez et al proposed real-time data streaming for vehicles in a smart city [ 69 ]. Their results revealed that Apache Kafka achieved a greater scalability, faster response, and reduced cost compared to traditional systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Integration of Apache Kafka and MongoDB can be utilized for real-time data processing for handling healthcare sensor data. Previous studies have shown that both technologies can be utilized for real-time data processing so that an incoming large volume of streaming data can be quickly handled, stored, and presented in real-time [ 69 , 70 ]. Thus, in our study, Apache Kafka and NoSQL MongoDB were used for real-time data processing to monitor the vital signs data from diabetic patients and presented in real time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As most of the mentioned platforms do not provide real-time data streaming analysis, an exciting contribution is the infrastructure that is described in [37]. The architecture was developed for real-time processing of data provided by vehicles in traffic, and for sending recommendations to drivers, using a simulator to test the scalability and response speed of the solution.…”
Section: Related Workmentioning
confidence: 99%
“…The result showed that Kafka achieves much higher throughput than conventional messaging systems (such as ActiveMQ and RabbitMQ) [28]. Fernandez-Rodriguez et al (2017) proposed real-time vehicle data streaming models for a smart city [29]. The proposed system gathers information from drivers in a big city, analyzing that information and sending real-time recommendations to improve driving efficiency and safety on roads.…”
Section: Open Source Technologies For Big Data Processingmentioning
confidence: 99%